Improving Early Childhood Learning Interest Ability Through Animation Media in Group B Students at Harapan Pammanu Kindergarten. - Jumiati Jumiati; Taqwa Taqwa; Rosdiana Rosdiana (Journal of Indonesian Islamic Studies, 2024)
This thesis discusses the Improvement of Early Childhood Learning Interest Ability Through Animation Media in Group B Students at Harapan Pammanu Kindergarten. The type of research used is Classroom Action Research (PTK), with two cycles, namely Cycle I which consists of 4 meetings and Cycle II which consists of 4 meetings. The success of this study is determined by the score of the research results which shows an increase in the learning interest ability of students. The score in the initial condition or pre-action was 6 students (30%) in the undeveloped category, 10 people (50%) in the developing category, and 4 people (20%) in the developing category as expected. In the first cycle with an average observation score, the number of students who began to develop amounted to 16 people (80%), and the number of students who developed according to expectations amounted to 4 people (20%). In Cycle II with an average observation score, students who developed according to expectations amounted to 3 people (15%), and students who developed very well amounted to 17 people (85%). Thus, this classroom action research (PTK) has succeeded in increasing children's interest in learning through animation media. Abstract contains a brief description of the problem and research objectives, methods used, and the results of research.